VD_FINDINFO Décision / 2015 / 552 vom 23. Juli 2015 - VD Tribunal cantonal (2015)
INTERNEMENTDROIT PÉNAL, LIBÉRATION CONDITIONNELLE, PROPORTIONNALITÉ, REJET DE LA DEMANDE | 56 CP, 64a CP, 26 LEP, 38 LEP